Assessing the effects of wind farms on soil organic carbon - Pekkan, Ozge Isik; Senyel Kurkcuoglu, Muzeyyen Anil; Cabuk, Saye Nihan; Aksoy, Talha; Yilmazel, Burcu; Kucukpehlivan, Tuncay; Dabanli, Ahmet; Cabuk, Alper; Cetin, Mehmet (Springer Science and Business Media LLC, 2021)
Wind energy is considered one of the cleanest and most sustainable resources among renewable energy sources. However, several negative environmental impacts can be observed, unless suitable sites are selected for the establishment of wind farms. The aim of this study is to determine the change in the soil organic carbon (SOC) stock resulting from land cover changes that were caused by wind farm establishments in the Karaburun peninsula. Within the scope of the study, remote sensing and geographic information system technologies were utilized. Maximum likelihood algorithm, one of the supervised classification techniques, was used to classify the land cover, and Normalized Difference Vegetation Index (NDVI) analyses were performed to determine land cover changes. The findings were correlated with the "Turkey Soil Organic Carbon Project" data. As a result, depending on the establishment of wind farms in the Karaburun Peninsula, a total decrease of 18,330.57 tons of SOC in the study area between 2000 and 2019 was determined. It should be taken into consideration that besides many other negative effects (effects on human health, effects on the ecosystem, effects on animals, etc.), land cover changes caused by wind farms may indirectly cause important problems such as climate change. Recently, this situation shows that there is an important dilemma in terms of current implementations. Wind farms are the most invested renewable energy sources and alternative energy supply to fossil fuels in terms of preventing climate change. However, the results of this study have reviewed that lack of proper approaches and methods to establish wind farms may result in various problems such as physical, chemical, and biological degradations and an increase in the amount of atmospheric carbon. Consequently, the investments in renewable energy sources should be comprehensively reevaluated in terms of current technologies, quality in the scope of environmental impact assessment and strategic environmental assessment processes, legal regulations and national policies, long-term environmental costs, etc.
Keywords: Energy-Generating Resources; Turkey; Health, Toxicology and Mutagenesis; General Medicine; Wind; Pollution; Carbon; Soil; Environmental Chemistry; Animals; Humans; Ecosystem; 2. Zero hunger; 15. Life on land; 7. Clean energy; 12. Responsible consumption; 13. Climate action; 11. Sustainability